The Effectiveness of Metacognitive Strategy in Teaching Listening Comprehension on Descriptive Text on Tenth Grader of Senior High School (RETAIN, 2018)
AbstrakTujuan dari penelitian ini adalah untuk mengetahui efektivitas dan perbedaan signifikan setelah implementasi strategi metakognitif dalam mengajar pemahaman mendengarkan pada teks deskriptif. Penelitian ini dirancang sebagai penelitian kuantitatif pre-eksperimental dan siswa kelas X-B Madrasah Aliyah Negeri 1 Pamekasan sebagai subjek penelitian. Try-out, pre-test, dan post-test digunakan sebagai instrumen untuk mengumpulkan data. Peneliti menganalisis data dengan membandingkan hasil pre-test dan post-test skor menggunakan rumus T-test pada SPSS 20. Hasil penelitian menunjukkan bahwa ada perbedaan signifikan setelah mengimplementasikan strategi metakognitif. Hal ini dapat dilihat dari skor pre-test dan post-test, nilai rata-rata pre-test 51,60 dan nilai rata-rata post-test 82,14. Dapat disimpulkan bahwa skor tes meningkat dan penggunaan strategi metakognitif mampu meningkatkan pemahaman mendengarkan siswa, karena strategi metakognitif dapat membantu proses siswa dalam merencanakan, memantau, dan mengevaluasi pembelajaran bahasa mereka untuk meningkatkan pemahaman mendengarkan mereka.Kata Kunci: Mendengarkan, Teks Deskriptif, Strategi Metakognitif AbstractThe aim of this study is to know the effectiveness and the significant difference of metacognitive strategy in teaching listening comprehension on descriptive text. This study was designed as a pre-experimental quantitative research and the students in class X-B of Madrasah Aliyah Negeri 1 Pamekasan were determined as the subject of the study. Try-out, pre-test, and post-test were used as an instrument to collect data. The researcher analyzed the data by comparing the results of pre-test and post-test score using T-test formula on SPSS 20. The result of the study showed that there was significance difference after the treatments given. It can be seen from the pre-test and post-test score, pre-test mean value 51.60 and post-test mean value 82.14. It means that the score of the tests had increased. It can be conclude that the use of metacognitive strategy was be able to improve students’ listening comprehension of the students, because Metacognitive strategy can help students’ process in planning, monitoring, and evaluating their language learning in order to improve their listening comprehension.Keywords: Listening, Descriptive Text, Metacognitive Startegy